Podejście procesowe a współczesne koncepcje i metody zarządzania organizacją - Nowosielski, Stanisław (Processing Approach to Contemporary Concepts and Organization Management Methods, 2008)
The article at first describes the essence, aims and profits of processing approach, which organization realizes owing to this approach. Next, it presents the division of concepts and management methods into three groups: connected with planning and control, organizing and related to quality management. The article, in a concise way, describes chosen concepts and methods and it also presents relations between process management and management methods and concepts. It also indicates special place and role of controlling concept in integrating different processing concepts and methods of management into united system of organization management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 58-70